GSTM1 and GSTM5 Genetic Polymorphisms and Expression in Age-Related Macular Degeneration*. (3rd March 2016) - Hunter, Allan A.; Smit-McBride, Zeljka; Anderson, Rachel; Bordbari, Matthew H.; Ying, Gui-shuang; Kim, Esther S.; Park, Susanna S.; Telander, David G.; Dunaief, Joshua L.; Hjelmeland, Leonard M.; Morse, Lawrence S.
ABSTRACT: Purpose : Previously, two cytosolic antioxidant enzymes, Glutathione S-transferase Mu 1 ( GSTM1) and Mu 5 ( GSTM5 ), were reduced in retinas with age-related macular degeneration (AMD). This study compared genomic copy number variations (gCNV) of these two antioxidant enzymes in AMD versus controls. Methods : Genomic copy number (gCN) assays were performed using Taqman Gene Copy Number Assays (Applied Biosystems, Darmstadt, Germany) in technical quadruplicate for both GSTM1 and GSTM5 . Peripheral leukocyte RNA levels were compared with controls in technical triplicates. Statistical comparisons were performed in SAS v9.2 (SAS Institute Inc., Cary, NC). Results : A large percentage of patients in both AMD and age-matched control groups had no copies of GSTM1 (0/0). The mean gCN of GSTM1 was 1.40 (range 0–4) and 1.61 (range 0–5) for AMD and control, respectively ( p = 0.29). A greater percentage of control patients had > 3 gCNs of GSTM1 compared with AMD, respectively (15.3% versus 3.0%, p = 0.004). The gCN of GSTM5 was 2 in all samples except one control sample. The relative quantification of GSTM1 and GSTM5 mRNA from peripheral blood leukocytes in patients showed significant differences in relative expression in AMD versus control ( p < 0.05). Peripheral blood leukocyte mRNA and gCN were not significantly correlated ( p = 0.27). Conclusion : Since high copy numbers of GSTM1 are found more frequently in controls than in AMD, it is possible that high copy number leads to increased retinal antioxidant defense. Genomic polymorphisms of GSTM1 and GSTM5 do not significantly affect the peripheral blood leukocyte mRNA levels.